An Investigation into Screening Process of Athletes during Basic Education School Sports Competitions and its Influence on Students’ Athletes in the Gomoa East District in Ghana - Sorkpor, Richmond Stephen; Cudjoe Agbeko, Adama Calvin; Jerry Agortey, Julius (International Journal of Scientific Research and Management (IJSRM), 2018)
This study sought to investigate the screening process of athletes for basic school sports competitions and its influences on students’ attitude towards Extracurricular Activities in the Gomoa East District. The study employed the descriptive survey design involving 150 respondents. The data collected was analyzed using descriptive statistic.  It was found out that, the respondents had a general positive perception about the screening process and therefore there is the need for a more scientific approach to the screening exercise to make it more robust and transparent to boost stakeholder’s confidence and continuous interest. It is therefore recommended that a more scientific approach should be adopted to reduce significantly the level of bias in the screening process